2012
DOI: 10.1007/s00221-012-3318-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rTMS over the left primary motor cortex on initiation and performance of a simple movement executed with the contralateral arm in healthy volunteers

Abstract: Repetitive transcranial magnetic stimulation (rTMS) affects cortical excitability according to the frequency of stimulation. Few data are available on the influence of rTMS applied over the primary motor cortex (M1) on motor performances in healthy volunteers. The aim of this study was to determine, through kinematic analysis, whether rTMS over the left M1 changes initiation and performance of movement executed with the contralateral arm. Nine healthy males completed a set of motor tasks, consisting of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This finding suggests either that the mechanisms and/or pathways targeted by iTBS are not altered in the aged brain or that plasticity is enhanced in older adults when attention is directed to the digit targeted by the stimulation. Interestingly, the findings of the current study also suggest that strategies implementing iTBS to facilitate plasticity with the goal of enhancing motor function [ 51 , 52 ] are likely to benefit young and older adults comparably. Critically, however, the factors determining an individual's response to iTBS, including the interaction between attention and age, require further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…This finding suggests either that the mechanisms and/or pathways targeted by iTBS are not altered in the aged brain or that plasticity is enhanced in older adults when attention is directed to the digit targeted by the stimulation. Interestingly, the findings of the current study also suggest that strategies implementing iTBS to facilitate plasticity with the goal of enhancing motor function [ 51 , 52 ] are likely to benefit young and older adults comparably. Critically, however, the factors determining an individual's response to iTBS, including the interaction between attention and age, require further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…This hypothesis seems to be supported by the significant effect we have on item 1 of the Disembodiment questionnaire (“It seemed like I was unable to move my hand”), which likely tests the sense of agency, with greater scores for rTMS than Sham session only in the Synchronous condition. Interestingly, previous studies (Di Lorenzo et al., ; Terao et al., ) showed that inhibitory (1 Hz) rTMS is effective in altering a motor output, as indexed by the showdown of movement production (i.e., increased reaction times, RT). Although we did not record RT here, we can speculate that, in the present experiment, the pairing of 1 Hz rTMS over M1 and the RHI procedure may have increased the feeling of being unable to move the hand.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that high post-stroke fatigue was associated with low motor cortical excitability2 but was not related to finger dexterity, grip strength, sustained attention index and information processing speed. However, suppressing motor cortical excitability can alter movement times as well as reaction times 3. Movement time reflects efficiency of cortical control of musculature that depends on primary motor cortex excitability,4 whereas reaction times reflect movement preparation along with a small component of the time for movement initiation 5.…”
Section: Introductionmentioning
confidence: 99%